Blood levels of cytokines in children with idiopathic partial and generalized epilepsy - Sonmez, Fatma Mujgan; Serin, Hepsen Mine; Alver, Ahmet; Aliyazicioglu, Rezzan; Cansu, Ali; Cane, Gamze; Zaman, Dilek (W B Saunders Co Ltd, 2013)
Purpose: Antiepileptic drugs have been reported to reduce the levels of serum immunoglobulins and affect the production and levels of certain cytokines. We investigated the effects of valproic acid (VPA) and topiramate (TPM) on the blood levels of interleukin (IL)-alpha, IL-1 beta, IL-6, IL-10, and TNF-alpha in children with idiopathic generalized and partial epilepsy. Methods: Forty prepubertal children aged 6-12 (mean 8.3 +/- 1.7) years, 19/40 (47.5%) female and 21/40 (52.5%) male, with idiopathic generalized or partial epilepsy diagnosed in the child neurology outpatient clinic were included. The patients were divided into two treatment groups: 20 were treated with VPA and 20 with TPM. The plasma levels of IL-1 alpha, IL-1 beta, IL-6, IL-10, TNF-alpha were measured using ELISA method before the initiation of treatment and at the 6th and 12th months of the treatment. The Chi-square test was used to compare qualitative data. To compare the periods, recurrence measurements were done using variance analysis and Freidman 2-sided variance analysis. p < 0.05 was considered as statistically significant. Results: In the VPA group, the levels of IL-1 alpha significantly increased at 12 months while the levels of IL-10 decreased at 6 months of treatment compared to values before treatment (p < 0.05). There was no significant difference in levels of IL-1 beta, IL-6, TNF-alpha (p > 0.05). In the TPM group, lower levels of IL-10 were observed at 6th and 12th months compared to the onset of treatment (p < 0.05). Conclusion: The results of this study demonstrated that VPA and TPM might lead to changes in the levels of cytokines in epileptic patients. The next step would be to investigate the relation of these findings to the outcome of epilepsy and response to treatment. (C) 2013 British Epilepsy Association. Published by Elsevier Ltd. All rights reserved.
Keywords: ILs; TNF-alpha; Topiramate; Valproic acid; Epilepsy; Child